ONLINE 2D SOCCER GAME USING SOCKS PROGRAMMING & AGENTS - MOHD SHAUKHI, MOHD KHAIRI (Universiti Teknologi PETRONAS, 2007)
A soccer game is designed to simulate a real soccer game that is played all over the world. The more realistic the game is, the more it will be played by people. The development of soccer games nowadays are moving towards creating 3D graphics that are almost human-like and artificial intelligence that are nearly perfect as a real soccer players. Some of them allow multiplayer gameplay which allows two people at different places connect to each other or to a game server and play the same game as opponent or teammates. This entire feature requires a personal computer which has fast processing power, a lot of memories, and a high-speed graphic processing chip. The objective of this project is to design a 2D soccer game which has the AI capability and multiplayer gameplay but only need minimum requirement to play it. To design such game, a lot of study and research had to be done in the field of artificial intelligence and networking. The scope of study also involves the research on the physics of the ball, such as the movement and interaction with other players. This system is developed using Visual ' Studio 2005 with the installment of Microsoft .NET 2.0 framework. Coding is done using WinSocks programming for the multiplayer mode, GDI+ Programming (.NET APis) for graphical details and Visual Basic language for AI and other features. All features in the game have meet the targeted requirements. There are still rooms for improvements mostly on the AI.